Multiple shifts to open habitats in Melastomateae (Melastomataceae) congruent with the increase of African Neogene climatic aridity - (:unkn) unknown (My University, 2018)
AimAfrican Melastomateae (Melastomataceae) comprise c. 185 species occurring in closed or open habitats throughout sub-Saharan Africa. We sought to reconstruct biogeographical and habitat history, and shifts in diversification rates of African Melastomateae using a well-sampled, dated molecular phylogeny.LocationAmericas, sub-Saharan Africa, Madagascar, SE Asia.TaxonAngiosperms, Melastomataceae, African Melastomateae.MethodsPhylogenetic relationships were estimated based on an extensive sampling of New and Old World Melastomateae, using two nuclear and three plastid markers. Divergence times were estimated in BEAST based on three calibration priors under Bayesian uncorrelated lognormal relaxed clock and birth–death speciation process. The dated phylogeny was used to infer the biogeographical history under a dispersal–extinction–cladogenesis model in “BioGeoBEARS”. The ancestral habitat of African Melastomateae was estimated using maximum likelihood and stochastic character mapping in “Phytools” and “ape” respectively. Finally, shifts in diversification rates were tested using BAMM.ResultsMelastomateae dispersed from South America to Africa during the Oligocene with subsequent dispersals to Madagascar and SE Asia during the Middle Miocene. Ancestral African Melastomateae were adapted to closed habitats with at least 12 shifts to open habitats occurring during the Middle Miocene or Pliocene. Speciation rates steadily increased since the Neogene, and none of the habitat shifts led to a significant increase in diversification rates.Main conclusionsLong-distance dispersal from South America during the Early Miocene explains the origin of African Melastomateae. The inferred adaptation to open habitats from an ancestrally closed habitat is congruent with the Neogene increase of aridity across Africa. The adaptation to open habitats during the Neogene is an important driver of African plant diversity, but is not always followed by increased d
Keywords: African Research